THE FORMING OF HRM PRACTICES IN INTERNATIONAL JOINT VENTURES IN THE CONTEXT OF COOPETITION- A Multiple- Case Study within a Finnish Industrial Company - Kaleva, Riikka (My University, 2009)
The purpose of this study was to find out the factors which impact the forming of HRM practices in the international joint ventures in the context of coopetition. Therefore, the main objective for the study was to identify and analyze the factors as well as focus on the subject by researching the internal and external factors and find out the significance of the coopetition in this context. The framework of the study consisted of the one main part, that is, focusing on the theory from two different perspectives. Firstly, the internal and external factors which impact the IJV were described. The focus was to concentrate on the Institutional theory by Scott (1985, 2001) which divides the external institutional pressure for regulative, normative and cognitive pillars and internal institutional factors for normative, coercive and mimetic pressures. Secondly, the control was discussed with the support of bargaining power and resource-dependence theory. The empirical part of the study consists of the methodology used for the qualitative case studies. The six respondents, equally both men and women, were interviewed for the study. The six respondents were either from the host-company or from the international joint venture related to it. The study includes two co-owned international joint ventures and one majority-owned joint venture. The empirical findings were discussed by using compare and contrast tables in which all the ventures were reflected to the theory, and the similarities and differences were researched. The reason for this was to compare them but also receive new knowledge about the researched theme. The results of the study indicated that there are plenty of factors which influence the forming of HRM practices in co-owned IJVs. Firstly, there are external and internal pressures which affect the formation. Some of the pressure is created by the parent companies in their host-countries, some in the local environment of the IJV. Secondly, the study pointed out that the institutional theory and control can explain the factors which affect the forming of HRM practices. Finally, the coopetition affects the formation because active cooperation increases the power of the parent companies in the IJV whereas competition reflects the control between the parent and IJV.
Keywords: IJV; HRM practice; Institutional theory; control; coopetition; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|